2017
DOI: 10.9755/ejfa.2017.v29.i10.1297
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality of Limousin young bulls slaughtered at 6, 9 and 12 months of age

Abstract: The aim of this study was to compare the quality of meat of the young Limousin bulls slaughtered at the age of 6, 9 and 12 months, with particular regard to the residual glycogen content in the meat and the value of the glycolytic potential. The study was conducted on bovine longissimus lumborum muscle. The residual glycogen content, glycolytic potential value (96 h post-mortem), pH value (45 min, 24 h, 48 h and 96 h post-mortem), IMP/ATP index (45 min post-mortem), colour parameters (L*, a* and b*), natural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This agrees with the findings of Yim et al ., but Ahnström et al . and Runowska et al . did not find any pH difference due to animal age.…”
Section: Resultsmentioning
confidence: 81%
“…This agrees with the findings of Yim et al ., but Ahnström et al . and Runowska et al . did not find any pH difference due to animal age.…”
Section: Resultsmentioning
confidence: 81%
“…The pH values were not influenced by the dietary supplementation of olive cake as observed by Ozdogan et al [38] in lambs fed with diets including different levels of olive cake. According to Czyzak-Runowska et al [39] an abnormally high final muscle pH (>6.0) results in the production of a dark-cutting or dark, firm, and dry (DFD) meat. Pipek et al [40] reported that a meat of high quality has ultimate pH at the range of 5.4-5.6.…”
Section: Discussionmentioning
confidence: 99%
“…Meat tenderness and cooking loss. Meat tenderness is a major quality characteristic that is highly correlated with the overall consumers' acceptance of beef (Czyżak-Runowska et al, 2017). The meat tenderness (kg/cm 2 ) of male Bali cattle fed with 12% CP and 72% TDN (T 1 group) was higher (P<0.05) than those of male Bali cattle fed 100% forage (T 0 group) and 15% CP and 72% TDN (T 2 group), which had relatively the same tenderness (Table 4).…”
Section: Meat Qualitymentioning
confidence: 99%